Exploring the Modus Operandi of Coaches Who Perpetrated Sex Offenses in Canada - St-Pierre, Elisabeth; Parent, Sylvie; Deslauriers-Varin, Nadine (Frontiers in Psychology, 2022)
This study investigated the modus operandi strategies employed by 120 coaches who committed sexual abuse towards 331 athletes under their authority. More than 2,000 Canadian court judgements and media reports were identified using online search databases. Using descriptive analysis, 51 strategies used in six modus operandi stages were identified. Results highlighted the most frequent strategies used by coaches for each stage of the crime commission process. Additionally, findings revealed the influence of the victims’ gender, coaches’ sport level and year of coaches' first offenses on modus operandi strategies used. Implications for crime prevention measures are discussed.